Composite Materials: Fatigue and Fracture (Third Volume) 1991
DOI: 10.1520/stp17732s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low-Velocity Impact on Composite Structures

Abstract: Composite materials are sensitive to out-of-plane loads because they are weaker through the thickness than in the plane of lamination. Consequently, composite structure subjected to impact may suffer significant damage, which results in a loss in strength. The effect of impact energy on different thicknesses of laminate with respect to ultimate compressive strength was evaluated using the NASA ST-1 specimen test. Impact damage was measured using ultrasonic C-scans and quality was assessed by visual observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This behavior exists until a plateau is reached, after which no further strength reduction is seen. Madan (1989) has also shown that thinner laminates required less energy to delaminate, but the plateau strength was approximately the same that of the thicker two laminates. The thermoplastic systems showed a 10% plateau strength improvement over the thermoset resins.…”
Section: III Delamination Damage In Aerospace Composites Often Thementioning
confidence: 86%
See 2 more Smart Citations
“…This behavior exists until a plateau is reached, after which no further strength reduction is seen. Madan (1989) has also shown that thinner laminates required less energy to delaminate, but the plateau strength was approximately the same that of the thicker two laminates. The thermoplastic systems showed a 10% plateau strength improvement over the thermoset resins.…”
Section: III Delamination Damage In Aerospace Composites Often Thementioning
confidence: 86%
“…investigations have been performed on low-velocity impact as another source of delaminations (Wanthal et al 1993;Chai 1982;Naval Air Development Center 1986;Madan 1989;Horton and Whitehead 1988;Ramkumar 1982;Williams 1984;Guynn and O'Brien 1985). Impact damage can occur at almost any time during the service lifetime of an aircraft.…”
Section: III Delamination Damage In Aerospace Composites Often Thementioning
confidence: 99%
See 1 more Smart Citation